2015
DOI: 10.5455/msm.2014.27.39-41
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Field Dependent-Independent Cognitive Style and Understanding of English Text Reading and Academic Success

Abstract: Background:The learning styles are the distinctive learners’ strategies for information processing and discovering new concepts. One of the most important kinds of learning styles is the Witkin’s theory of field dependence-independence cognitive style.Objective:This study seeks to find the relationship between field dependence –independence cognitive style and English text reading comprehension, learning English as a foreign language, academic achievement and the choice of academic courses.Methods:In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Students who have different cognitive styles will also have a different way of understanding the text when involving in reading activities. This is true because some studies have shown the relationship between the students' cognitive style with their success in academic study (Witkin, et al, 1977), and more specifically in reading ability (Nozari and Siamian, 2014). Nozari and Siamian (2014) who conducted the research on investigating the relationship between field dependent-independent cognitive styles and understanding of English text reading and academic success find that field independent (FI) cognitive styles determine the change of reading comprehension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who have different cognitive styles will also have a different way of understanding the text when involving in reading activities. This is true because some studies have shown the relationship between the students' cognitive style with their success in academic study (Witkin, et al, 1977), and more specifically in reading ability (Nozari and Siamian, 2014). Nozari and Siamian (2014) who conducted the research on investigating the relationship between field dependent-independent cognitive styles and understanding of English text reading and academic success find that field independent (FI) cognitive styles determine the change of reading comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…This is true because some studies have shown the relationship between the students' cognitive style with their success in academic study (Witkin, et al, 1977), and more specifically in reading ability (Nozari and Siamian, 2014). Nozari and Siamian (2014) who conducted the research on investigating the relationship between field dependent-independent cognitive styles and understanding of English text reading and academic success find that field independent (FI) cognitive styles determine the change of reading comprehension. It means that the more the FI, the higher the reading comprehension skills and learning English and the more academic achievement will result.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the cognitive style correlates with reading comprehension score, English language learning and academic achievement with coefficient of determination of 8.8%, 9.2% and 11 .6% respectively. [15] Wu et al (1993) focused on the relationship between cognitive style and English grades. 250 English major students were enrolled.…”
Section: Studies On the Relationship Between Fd-fi Cognitive Style And English Reading Comprehensionmentioning
confidence: 99%
“…Different experiences in the basic education make IMSs differ from domestic students in the learning obstacles and learning style preferences (17,18), such as communication Correspondence: Y.-F. Wang (yufengwang@ems.hrbmu.edu.cn); V. Parpura (vlad@uab.edu). Submitted 5 October 2020 / Revised 2 February 2021 / Accepted 24 February 2021 between IMSs and teachers of host institution, etc.…”
Section: Introductionmentioning
confidence: 99%